Inscriptions with images or images with didascaliae? Liria’s vase (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
There are two basic types of the Liria ceramic inscriptions, the long and the brief inscriptions. The long ones are original from Liria and present a characteristic vocabulary. The briefs ones seem to be didascaliae. The long inscriptions correspond plausibly to a type of epigraph usually not taken into consideration, the literary and didactic epigraphs. The length, the places of discovery, the scenes accompanying the inscriptions and the structure of the beginning of the inscription in the cases preserved support this hypothesis, while the usual consideration of Liria's vessels as self-assertion of an aristocracy is reinforced with it.
Keywords: Liria; Edeta; Ceramics; Dipinti; Epigraphical Typology; Iberian Language; Syntactic Patterns; Originality